EFFECT OF BOARD ATTRIBUTES ON CORPORATE TAX PLANNING AMONG LISTED MANUFACTURING COMPANIES IN NIGERIA - Saheed Lawal (Malete Journal of Accounting and Finance)
Ineffective governance structures, like excessively large boards and a lack of gender diversity, hinder decision-making and tax compliance, leading to suboptimal tax planning practices. This study examined the effect of board attributes on corporate tax planning among listed manufacturing companies in Nigeria using an ex-post facto research design and data from annual reports and financial statements for 2017 to 2023. The population of the study consists of listed manufacturing companies on the Nigerian Stock Exchange. There are 43 companies listed on the Nigerian Stock Exchange Market as of 31st December 2023.A census sampling technique was used to select the sample size for the study. Thus, the study filtered the sample firms using the following two-point filter. Thereafter, all firms that scaled the filter was selected using census sampling. Multiple regression analysis revealed that board size, CEO tenure, gender diversity, and board independence positively impact corporate tax planning. Based on the results presented, the study concludes that corporate board size, gender diversity, CEO tenure and board independence encourage tax planning practices. The study recommends women's participation on boards to promote effective tax planning. Diverse boards improve decision-making and innovation, while CEO tenure can reduce tax liability. Although the impact of women on tax planning is minimal, prioritizing independent directors is essential for influencing tax strategies effectively.